N of 1 trials. Practical tools for medication management. - Nikles, C; Glasziou, P; Mar, D; Duggan, C; Mitchell, G (2000)
BACKGROUND: In single patient (n of 1) trials, a patient acts as his or her own control in a study comparing the effectiveness of a drug with placebo or another drug. The aim of a single patient trial (SPT) is to identify the best treatment for the individual patient, formalising a 'trial of treatment' by using blinding and multiple crossover periods. OBJECTIVE: We have successfully piloted SPTs for osteoarthritis and attention deficit hyperactivity disorder, and several others are currently being piloted. Barriers encountered include: obtaining identical placebos, ethical approval for individual SPTs, standardising doses, determining length of treatment periods, patient withdrawals and cost of the SPTs. DISCUSSION: Only prescribing medications if an individual has been shown to be a responder can greatly benefit general practitioners, patients and the healthcare system. We have established the infrastructure necessary to offer a single patient trial service to GPs and patients anywhere in Australia. This has the potential to revolutionise prescribing for certain chronic conditions.